PJOK Management Based on the 2013 Revised 2018 Curriculum At the Elementary Schools, Sandai District, West Kalimantan Province (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
This research is motivated by implementing the 2013 curriculum, which raises various kinds of teacher perceptions, so that teachers have difficulty in studying, interpreting and describing the 2013 curriculum. Analyzing management planning, implementation, learning evaluation and supervision of PJOK teachers. This study uses a naturalistic qualitative research design, so the research aims to describe the actual field conditions regarding PJOK Teacher Management based on the 2013 Revised 2018 Curriculum, Sandai District. The results, in general, teachers of PJOK Elementary Schools in Sandai sub-district are in lesson planning, many teachers make devices by photocopying other people, some are downloaded themselves but printed out directly without being adjusted to field conditions. In implementing learning, the teacher cannot make the best use of the time possible, because the number of students who exceeds the capacity of the teacher in the learning group is only 20 to 28 students, but in some schools there are still teachers teaching 1 meeting reaching 50 to 70 students. Learning Evaluation There are teachers who carry out process evaluations, there are also teachers who carry out evaluation of results, but there are also teachers who carry out process and outcome evaluations. Supervision of teachers can be said that there are still principals who do not understand and even do not carry out their roles and functions as school principals, this causes teachers to feel they do not have a burden on their duties as teachers and the supervision carried out by school supervisors towards teachers is not running properly because supervisors are too focused on the supervision of the principal and of the school as a whole.